2012
DOI: 10.5194/acp-12-9529-2012
|View full text |Cite
|
Sign up to set email alerts
|

Observations of glyoxal and formaldehyde as metrics for the anthropogenic impact on rural photochemistry

Abstract: We present simultaneous fast, in-situ measurements of formaldehyde and glyoxal from two rural campaigns, BEARPEX 2009 and BEACHON-ROCS, both located in Pinus Ponderosa forests with emissions dominated by biogenic volatile organic compounds (VOCs). Despite considerable variability in the formaldehyde and glyoxal concentrations, the ratio of glyoxal to formaldehyde, R<sub>GF</sub>, displayed a very regular diurnal cycle over nearly 2 weeks of measurements. The only deviations in R<sub>GF</su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
59
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 61 publications
13
59
0
Order By: Relevance
“…However, based on the in situ observations, DiGangi et al (2012) found that the anthropogenic emissions have positive impact on R GF . Our model study at the BG site indicate that the influence of anthropogenic emissions on R GF is rather complicated.…”
Section: Influences On the Chocho To Hcho Ratiomentioning
confidence: 99%
See 4 more Smart Citations
“…However, based on the in situ observations, DiGangi et al (2012) found that the anthropogenic emissions have positive impact on R GF . Our model study at the BG site indicate that the influence of anthropogenic emissions on R GF is rather complicated.…”
Section: Influences On the Chocho To Hcho Ratiomentioning
confidence: 99%
“…5), high R GF is usually found in early morning and a sharp decrease of R GF is identified shortly after sunrise. This DiGangi et al (2012) at a rural site in the USA. Our model shows that P CHOCHO /P HCHO of aromatic compounds (e.g., benzene, toluene, m,p-xylene) are more than 3 times larger than that of isoprene.…”
Section: Influences On the Chocho To Hcho Ratiomentioning
confidence: 99%
See 3 more Smart Citations